Tingkat Pengetahuan Tentang Penggunaan Antibiotik Masyarakat Desa Kajoran Kecamatan Klaten Selatan - Avanillla Fany Septyasari; Aristhasari Putri; Hanna Nikma Fatin; Choiril Hana Mustofa; Muchson Arrosyid (CERATA Jurnal Ilmu Farmasi, 2025)
Antibiotics are one type of medication used to treat bacterial infections. The use of antibiotics will ensure successful treatment, but currently there are many cases of antibiotic resistance caused by the inappropriate use of antibiotics. The purpose of this study is to determine the level of knowledge among the community of Kajoran Village, South Klaten District, regarding the use of antibiotics. The method used was descriptive observational with a cross-sectional approach and purposive sampling technique. The research instrument used a questionnaire and analysis using univariate analysis. The results showed that the level of knowledge among the community in Kajoran Village, South Klaten District was in the category of sufficient knowledge regarding the use of antibiotics (42.3%).